Reševanje treh velikih starogrških problemov - Jerman, Marjan (Obzornik za matematiko in fiziko, 2012)
The three classical ancient Greek problems, doubling the cube, squaring the circle and trisecting an angle cannot be solved using ruler and compass only. Some interesting ancient non-standard solutions of these problems are described.
Keywords: antična matematika; kvadratura kroga; podvojitev kocke; trisekcija kota